Character Value Formation Through Malay Gambus Art in “Mesjid Mekkah" Song - Laila Fitriah; M. Jazuli; Wadiyo Wadiyo; Eko Sugiarto (MUMTAZ : Jurnal Pendidikan Agama Islam, 2025)
The contemporary character crisis has raised a profound concern to Indonesian way of living. The spike oftechnological advancement has brought both positive and negative impact to the young generation. The government, on the other hand, has started to prioritize cultivating of character programme in each educational institution, particularly in Gambus music art. This research aims to explain character value cultivation in Malay Gambus art. This research was conducted at Pekanbaru City, with performing arts students of Islamic Riau University as the research subjects, and Riau Malay Gambus Art as the research object. This research had been done in a qualitative descriptive methods by using observation, interview, literature review and documentation while data analysis involved primary and secondary data that were gathered using qualitative descriptive method. The research results have revealed that the students who arestudying Gambus art tend to have more understanding on character cultivation values and practice those values in their daily life compared to the students who are not studying Gambus art. In addition, character cultivation values in Gambus art can be divided into: Religious Value, Truth Value, Tolerance Value, Discipline, Creative and Democratic Value. There are a lot of messages and values gained from Gambus Art that are derived from its religious and moral functions which are applicable to everyday life. Therefore, values contained in the Gambus Art itself support the character cultivation in the young generation.